A parametric approach to estimate the green bond premium - Schmitt, Stephan Jakob (2018)
We analyze whether green bonds are traded on a premium versus conventional issuances of the same issuer. We estimate the difference in yield between a sample of 160 green bonds and a synthetic conventional bond with identical characteristics. The paper finds that green bonds have been traded on slightly higher yields than conventional bonds. This premium seems to decline in 2016 and 2017. Our data suggests that there is no significant difference between the developed and emerging markets and between different industry groups.